A longitudinal investigation of repressive coping and ageing. (2nd October 2016) - Erskine, James; Kvavilashvili, Lia; Myers, Lynn; Leggett, Sarah; Davies, Steve; Hiskey, Syd; Hogg, Joanna; Yeo, Sophia; Georgiou, George
Abstract : Objectives: Two studies investigated the possibility that repressive coping is more prevalent in older adults and that this represents a developmental progression rather than a cohort effect. Study 1 examined repressive coping and mental health cross-sectionally in young and old adults. Study 2 examined whether there was a developmental progression of repressive coping prevalence rates in a longitudinal sample of older adults. Method: Study 1 compared younger adults (mean age 27.6 years) with older adults (mean age 74.2 years) on inventories of mental health and well-being and examined the prevalence of repressive coping in both samples. Study 2 re-tested a sample of older adults previously reported following an interval of 7 years. Results and conclusion: Study 1 – in line with previous research older adults demonstrated greater psychological well-being and had a higher prevalence of repressive coping than younger adults (at 30% vs. 12% respectively). Study 2 – the data indicated that the prevalence of repressive coping rose from 41% at the first time of testing (2002) to 56.4% at the second testing interval (2009). These results suggest that repressive coping may increase across the lifespan in certain individuals and continue to increase throughout older adulthood. Furthermore, this increase in repressive coping with age appears to result in better well-being in those older adults who become repressive copers.